Application of the Trend Moment Method to Predict Shoes Sales - Gilang Nugroho Syahputra Jarod; Iqbal Kamil Siregar; Endra Saputra (Sistemasi: Jurnal Sistem Informasi, 2023)
The N+2 Fashion store is engaged in selling trend shoes which is located in Air Batu City. Activities in the N+2 Fashion Store include ordering and selling trending shoes. Checking the supply of trending shoes is done by checking them one by one, of course this will make it very difficult for employees to estimate the number of trend shoes they want to order from each trending type of shoe. The large number of trend shoe brands is an obstacle in carrying out business processes which results in wrong prices for these trend shoes. In predicting trend shoes must ensure the sales process, minimize costs and time required. The problem faced by the N+2 Fashion Store is the difficulty in predicting the number of items that must be available for the next period in order to meet customer needs and not cause a buildup of goods in the long term. To overcome this problem, predictions are made using the trend moment method which is a forecasting method used to see trends (data that have increased) based on historical data from one variable using time series data. The results of the research obtained a prediction that in September 2022 there would be 9 pcs of Adidas shoes sold with a MAPE error rate of 16.33%.